Modification of Bacterial Effector Proteins Inside Eukaryotic Host Cells - Popa, Crina M.; Tabuchi, Mitsuaki; Valls, Marc (Frontiers in Cellular and Infection Microbiology, 2016)
Pathogenic bacteria manipulate their hosts by delivering a number of virulence proteins -called effectors- directly into the plant or animal cells. Recent findings have shown that such effectors can suffer covalent modifications inside the eukaryotic cells. Here, we summarize the recent reports where effector modifications by the eukaryotic machinery have been described. We restrict our focus on proteins secreted by the type III or type IV systems, excluding other bacterial toxins. We describe the known examples of effectors whose enzymatic activity is triggered by interaction with plant and animal cell factors, including GTPases, E2-Ubiquitin conjugates, cyclophilin and thioredoxins. We focus on the structural interactions with these factors and their influence on effector function. We also review the described examples of host-mediated post-translational effector modifications which are required for proper subcellular location and function. These host-specific covalent modifications include phosphorylation, ubiquitination, SUMOylation, and lipidations such as prenylation, fatty acylation and phospholipid binding.